2013
DOI: 10.1530/joe-13-0167
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in PAPP-A show resistance to the development of diabetic nephropathy

Abstract: We investigated pregnancy-associated plasma protein-A (PAPP-A) in diabetic nephropathy. Normal human kidney showed specific staining for PAPP-A in glomeruli, and this staining was markedly increased in diabetic kidney. To assess possible contribution of PAPP-A in the development of diabetic nephropathy, we induced diabetes with streptozotocin in 14-month-old wild-type (WT) and PAPP-A knock-out (KO) mice. Renal histopathology was evaluated after four months of stable hyperglycemia. Kidneys from diabetic WT mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…PAPP-A was reported to be higher in T2DM than healthy controls in 2 studies [15, 16], appeared to be negatively associated with HbA1C levels [49], and its expression in glomeruli was associated with diabetic nephropathy [50]. Our study found significantly higher concentrations of PAPP-A in ACS patients with T2DM than those without (19 vs. 13 ng/ml, p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…PAPP-A was reported to be higher in T2DM than healthy controls in 2 studies [15, 16], appeared to be negatively associated with HbA1C levels [49], and its expression in glomeruli was associated with diabetic nephropathy [50]. Our study found significantly higher concentrations of PAPP-A in ACS patients with T2DM than those without (19 vs. 13 ng/ml, p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…Diabetic nephropathy is another pathological condition that may develop as a consequence of increased PAPP-A activity. In humans, diabetic nephropathy is associated with an elevated level of glomerular PAPP-A expression, and the absence of PAPP-A in mice confers resistance to the development of pathological hallmarks of diabetic nephropathy (Mader et al 2013).…”
Section: Possible Pathophysiological Roles and Therapeutic Targeting mentioning
confidence: 99%
“…We have previously reported that PAPP-A knock-out mice show decreased incidence and severity of age-related nephropathy (13). Also, 14-month-old female PAPP-A knock-out mice were resistant to experimentally-induced type 2 diabetic nephropathy (8). We had chosen female mice to do the latter studies, since the preliminary data coming out of this study indicated higher levels of PAPP-A expression in females compared to males, and, thus, we reasoned that there might be a greater effect of PAPP-A gene deletion in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest not only diagnostic and prognostic value, but also potential therapeutic value for PAPP-A. Indeed, in the mouse, global deletion of PAPP-A has been shown to have beneficial effects promoting resistance to atherosclerotic plaque progression, visceral fat accumulation and diabetic nephropathy (8,10,11), and in the maintenance of immune competence with age (12). Furthermore, these PAPP-A knock-out mice live significantly longer than wild-type littermates (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation